Mixed convection and entropy production in a nanofluid-filled closed space with inclined magnetic field - Hussain, Shafqat; Öztop, Hakan Fehmi; Mehmood, Khalid; Ali, Mohamed E. (Springer, 2019)
A computational analysis has been performed to study the impact of magnetic field on entropy generation due to mixed convective nanofluid flow with top and bottom side moving lid-driven closed space. The sinusoidal heating was applied to left vertical side, while the right side was under lower constant temperature. Top and bottom sides move in the opposite direction in lateral axis. A monolithic Galerkin finite element approach has been adopted for the spatial discretization and the Crank-Nicolson for the temporal integration of various values of the governing parameters such as magnetic field inclination angle (0 degrees <=gamma <= 90 degrees), Hartmann number (0 <= Ha <= 100), Richardson number (0.01 <= Ri <= 10) and nanoparticle volume fraction (0 <=phi <= 0.04). Thus, heat and fluid flow and entropy generation results are presented. It is found that inclination angle of magnetic field plays significant role in fluid flow and heat transfer, and entropy generation is affected slightly by variation of nanoparticles volume fraction. Heat transfer increases almost 400% with the increase in Reynolds number.
Keywords: Inclined magnetic field; Mixed convection; Entropy generation; Lid-driven cavity; monolithic Galerkin FEM; Numerical simulation